The Effect of Computerization Systems on Employee Performance in Duren Sawit Office, East Jakarta - Andrie Kurniawan; Ahmad Taufik; Andi Diah Kuswanto (Kusuma Negara Business School, 2020)
Technological developments have affected services to the community more quickly and accurately. The computerized system has been proven to assist the government in smoothing the operational work of its employees. This study aims to determine the significant effect of a computerized system on employee performance at the Duren Sawit office in East Jakarta, and to determine the responses of employees in the community service department who use a computerized system. The research method used in this research is a quantitative descriptive approach. Data obtained from the results of questionnaires given to respondents and interviews of 30 people with census sampling techniques, namely front office employees. The office of the village of Duren Sawit uses a computerized system to help smooth operational work of its employees in serving the community. From the results of processed questionnaires, observations, and interviews, it can be seen that there is a significant influence between the computerized system on the performance of public service employees which is very strong with a very strong correlation coefficient value, with a variable influence of 84.6%. As well as the response of employees who use a computerized system, proving that the system used is very helpful in completing their work so as to produce good performance.